Solid-state 1H spin polarimetry by 13CH3 nuclear magnetic resonance - S. J. Elliott; S. J. Elliott; Q. Stern; S. Jannin (Magnetic Resonance, 2021)
Dissolution dynamic nuclear polarization is used to prepare nuclear spin polarizations approaching unity. At present, 1H polarization quantification in the solid state remains fastidious due to the requirement of measuring thermal equilibrium signals. Line shape polarimetry of solid-state nuclear magnetic resonance spectra is used to determine several useful properties regarding the spin system under investigation. In the case of highly polarized nuclear spins, such as those prepared under the conditions of dissolution dynamic nuclear polarization experiments, the absolute polarization of a particular isotopic species within the sample may be directly inferred from the characteristics of the corresponding resonance line shape. In situations where direct measurements of polarization are complicated by deleterious phenomena, indirect estimates of polarization using coupled heteronuclear spins prove informative. We present a simple analysis of the 13C spectral line shape of [2-13C]sodium acetate based on the normalized deviation of the centre of gravity of the 13C peaks, which can be used to indirectly evaluate the proton polarization of the methyl group moiety and very likely the entire sample in the case of rapid and homogeneous 1H–1H spin diffusion. For the case of positive microwave irradiation, 1H polarization was found to increase with an increasing normalized centre of gravity deviation. These results suggest that, as a dopant, [2-13C]sodium acetate could be used to indirectly gauge 1H polarizations in standard sample formulations, which is potentially advantageous for (i) samples polarized in commercial dissolution dynamic nuclear polarization devices that lack 1H radiofrequency hardware, (ii) measurements that are deleteriously influenced by radiation damping or complicated by the presence of large background signals and (iii) situations where the acquisition of a thermal equilibrium spectrum is not feasible.